APLIKASI ANIMASI 2D SEBAGAI MEDIA PEMBELAJARAN OLAHRAGA SENAM BERBASIS DESKTOP - Jatmiko, Febrian Rio Parikesit; Yuliana, Ade (Jurnal Mahasiswa Terapan, 2025)
Gymnastics learning media for children at Triaslingga Kindergarten is very interesting for students and is very important in supporting physical and mental development. This media is designed to meet the needs of children in understanding basic gymnastic movements, improving motor skills, and encouraging fun physical activity. The approach used in developing this media is an active learning method that involves games and social interaction. We also tested the media on a group of children to evaluate its effectiveness in increasing their interest and understanding of gymnastics. The results show that the use of varied media can increase children's engagement, as well as their ability to perform gymnastic movements well. The research method used for learning media applications uses MDLC. The results of this research are kindergarten children understand the movements of penguin gymnastics and duck gymnastics.